Chemical composition, microstructure and sintering temperature modifications on mechanical properties of TiC-based cermet – A review. (15th February 2015) - Rajabi, A.; Ghazali, M.J.; Daud, A.R.
Highlights: Composition, grain size and sintering temperature are vital in TiC-based cermets. Nano-TiN plays important role in increasing the performance of the cermets. Decrease of core-rim thickness improves mechanical properties in the cermets. Increase in carbide stoichiometry in Ti(CN) decreases the wear rate. Increase of sintering temperature above 1430 °C, the decomposition of TiN occurs. Abstract: Cermets, particularly those based on TiC, are receiving considerable attention because of their unique properties, including high hardness and resistance to thermal deformation. However, TiC-based cermets lack sufficient toughness. To improve the performance of these cermets, numerous studies have been conducted to determine the factors that can be manipulated to improve their toughness. However, the results of these studies vary. This paper summarizes the studies to improve cermet design via chemical compositions and microstructures. Critical issues including the effects of grain size and sintering temperature on the mechanical properties (i.e., toughness, hardness, and wear resistance) of TiC-based cermets are also discussed.